Study on Weeds Abundance on Rice Fields in Mycorrhizal Inoculation and Different Planting Methods - Listyowati, Charisnalia; Indradewa, Didik; Irwan, Siti Nurul Rofiqo (Sebelas Maret University, 2022)
The increasing demand for rice and the increasing population growth rate require sustainable rice production. Direct seeding of rice (DSR) combined with the use of arbuscular mycorrhizal fungi (AMF) is needed to achieve sustainable food production. This study aims to determine the effect of the planting method and mycorrhizal inoculation on the diversity, composition and dominance of weeds in a rice field for the sustainability of agricultural production. The research used a split-plot design with three replications. The main plot was the planting method consisting of on row, drum seeder and transplanting, while the subplot was mycorrhizal inoculation divided into with mycorrhizal inoculation and without mycorrhizal inoculation. The observed variables were light penetration, weeds population, weeds composition, weeds biomass, summed dominance ratio and community coefficient. The results showed that there were 34 kinds of weeds consisting of 13 families and the dominant weed was annual weeds, most of which were broadleaf weeds. The dominant weed was Alternanthera sessilis (L.) R. Br. ex DC. (sessile joyweed). The planting methods affected the weed population in 24 days after sowing (DAS) and the composition of broadleaf weeds in 24 DAS but did not affect weed biomass. The AMF inoculation did not affect weed population, composition, or biomass. It is necessary to find mycorrhizal species that can affect weed growth. © 2022 Universitas Sebelas Maret.